Population and status of Emperor Geese along the north side of the Alaska Peninsula - Petersen, Margaret R; Gill, Robert E, Jr (Wildfowl, 1982)
We gathered information on the timing of spring and autumn migration of Emperor Geese Anser canagicus from Nelson Lagoon, the age ratios of geese during autumn migration, and the numbers of geese in estuaries along the north side of the Alaska Peninsula and Bristol Bay during spring and autumn migration. Birds staged in most of the lagoons and bays along the north side of the Alaska Peninsula, but Nelson Lagoon and Seal Islands Lagoon were the most heavily used. Geese concentrated in Nelson Lagoon for about six to eight weeks in both spring and autumn. We suspect that the population of Emperor Geese in Alaska may have declined by as much as 34% between the 1960’s and l981. Although the average number of young per successful breeding pair has remained high during this period, the overall proportion of young in the population has been extremely low, at least during the past five years. More studies are necessary to determine factors influencing the status of this species.